2021
DOI: 10.3390/diagnostics11050746
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance and Usability of the Genedrive® HCV ID Kit in Two Decentralized Settings in Cameroon and Georgia

Abstract: Point-of-care diagnostics have the potential to increase diagnosis and linkage to care and help reach the WHO targets to eliminate hepatitis C virus (HCV) by 2030. Here, we evaluated the diagnostic accuracy of Genedrive HCV ID assay for the qualitative detection of HCV RNA in decentralized settings in two low- and middle-income countries using fresh plasma specimens from 426 participants. The Abbott RealTime HCV assay was used as the gold standard. Genedrive HCV ID assay was conducted by different users. Users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This test can be operated outside of a laboratory but involves 12 manual steps. Its limit of detection is 2362 IU/mL, it can detect the most common HCV genotypes and subtypes, and its sensitivity and specificity compared with laboratory HCV RNA detection methods range from 96.2 to 100% and 99.5 to 100%, respectively [134][135][136]. Similarly, the Xpert HCV Viral Load kit that operates on the Cepheid GeneXpert instrument detects HCV RNA from plasma samples in 105 min but requires no manual steps after addition of the sample to the test cartridge.…”
Section: Hepatits C Virusmentioning
confidence: 99%
“…This test can be operated outside of a laboratory but involves 12 manual steps. Its limit of detection is 2362 IU/mL, it can detect the most common HCV genotypes and subtypes, and its sensitivity and specificity compared with laboratory HCV RNA detection methods range from 96.2 to 100% and 99.5 to 100%, respectively [134][135][136]. Similarly, the Xpert HCV Viral Load kit that operates on the Cepheid GeneXpert instrument detects HCV RNA from plasma samples in 105 min but requires no manual steps after addition of the sample to the test cartridge.…”
Section: Hepatits C Virusmentioning
confidence: 99%
“…Although the Cepheid platform is already used in the US for the diagnosis of other infections [ 44 ], this test is not yet FDA approved. The Genedrive HCV ID Kit (Genedrive Diagnostics, Manchester, United Kingdom) detects HCV RNA in 90 minutes using a small volume of plasma (30 μL) [ 45 , 46 ]. It has been tested in low-resource settings including the countries of Cameroon, Georgia, and India.…”
Section: What Is Workingmentioning
confidence: 99%
“…It has been tested in low-resource settings including the countries of Cameroon, Georgia, and India. The TrueNAT HCV RNA assay (Molbio Diagnostics, Goa, India) [ 45 , 46 ] has pooled sensitivity and specificity reported at 95% and 99%, respectively [ 31 ]. The SAMBA II HCV Qualitative Whole Blood test (Diagnostics for the New World, Birmingham, United Kingdom), tested in Ukraine reported a 96% sensitivity and 100% specificity [ 47 ].…”
Section: What Is Workingmentioning
confidence: 99%
“…Importantly, the HCV ID assay cartridge is not fully integrated into the system and requires several manual steps and precise pipetting. The assay performance has been evaluated in several studies, including studies conducted in resource-limited settings and primary healthcare facilities [ 24 ], which demonstrated that the assay has a sensitivity of 99% (95% CI, 98%–100%) and a specificity of 100% (95% CI, 99%–100%) [ 20 ]. Unfortunately, despite its good performance, the product was recently discontinued.…”
Section: Near Point-of-care Assays For Hcv Detectionmentioning
confidence: 99%